Reproducibility of nasal allergen challenge responses in adults with allergic rhinitis - Pantin CT; Southworth T; Wetzel K; Singh D (Dove Medical Press, 2019)
Charles T Pantin,1 Thomas Southworth,1 Kristiane Wetzel,2 Dave Singh1 1Medicines Evaluation Unit, Manchester Academic Health Science Centre, Manchester University NHS Foundation Trust, University of Manchester, Manchester, UK; 2Translational Medicine and Clinical Pharmacology, Boehringer Ingelheim Pharma GmbH & Co. KG, Biberach an der Riss, Germany Background: Allergic rhinitis is characterized by nasal inflammation in response to allergen exposure. Nasal allergen challenges are used in clinical trials evaluating drug effects. Reproducibility of nasal secretion cytokine responses and physiological measurements are needed to determine the optimum measurements and power calculations for future studies. We have investigated the reproducibility of nasal cytokine measurements, using ready-to-use polyvinyl acetate sponges to collect nasal secretions, and measurements of nasal physiological responses.Methods: Twelve subjects with allergic rhinitis and no history of respiratory disease, and 12 subjects with asthma and allergic rhinitis underwent a nasal allergen challenge. This was repeated at 7–14 days later.Results: There were increases in IL-5, CCL11, and CXCL8 responses post-challenge (all P<0.05). There was better reproducibility at later time points when higher cytokine levels were detected for IL-5 (ri =0.64 at 8 hours) and CXCL8 (ri =0.91 at 8 hours). Acoustic rhinometry provided good to excellent reproducibility (ri =0.66–0.89). Rhinomanometry had lower reproducibility with greater variation (ri =0.10–0.70), with some subjects unable to perform the measurement. Multiplex immunoassays provided greater sensitivity for CCL11 measurements. There were no differences between allergic rhinitis patients with and without asthma.Conclusion: Polyvinyl acetate sponges are a practical and reproducible way to sample nasal secretions. Acoustic rhinometry is a practical and reproducible method for assessing physiological responses. There were no differences in nasal response due to the presence of concurrent asthma. Keywords: acoustic rhinometry, total nasal symptom score, polyvinyl acetate sponges, IL-5, CXCL8, CCL11